Molecular identification and evolutionary relationships of Pomacea nobilis, basis for the specific authentication of the black apple snail from Peruvian Amazonia - Ramírez, Rina (2020)
In the Peruvian Amazon, freshwater snails of the Ampullariidae family are known as churos, and around 20 species have originally been described for Peru. Although they are widely used for food, traditional medicine and the object of many studies for their cultivation and industrialization, only the species Pomacea maculata is mentioned in the literature. Molecular identification was carried out based on the mitochondrial marker COI of individuals of "churo negro" apple snails (Pomacea) commercialized in the markets of Iquitos, as well as those used in restaurant dishes in the city of Lima, and contrasted with specimens from their natural habitat. It was found that these specimens, correspond to the species Pomacea nobilis (Reeve, 1856). The molecular phylogenetic analysis showed P. nobilis as the sister species of P. guyanensis, in the P. glauca group, distantly related to P. maculata. The uncorrected distances found between them, for the mitochondrial marker COI, were from 11.33% to 13.17%, while with P. maculate were from 13.67% to 15.33%. These results demonstrated the effectiveness of the DNA barcode for the identification and authentication of the species, which gives it added value for its eventual export trade.